What is the Role of Partial Compliance in Moral Theory? - Rivera López, Eduardo Enrique (2022)
The problem of nonideal theory has been widely discussed in political philosophy in recent times. The problem has received much less attention, however, at the level of individual morality. Since the real world is a nonideal one, the problem is extremely relevant, if moral theory is to guide our action as moral agents. My purpose in this paper is mainly conceptual. I first clarify the distinction between different kinds of nonideal situation (natural accidents or limitations and partial compliance with morality) and how different moral theories face those different kinds of imperfections. Secondly, I try to show that the distinction between the two main sources of imperfection is less straightforward and more complex than might be expected. Finally, I suggest that the role of partial compliance in nonideal moral theory is much more modest and difficult to defend than we might at first think.